Zachowania zdrowotne chorych z marskością wątroby = Health behaviours of patients with cirrhosis of the liver - Sierpińska, Lidia; Zielińska, Katarzyna (Journal of Education, Health and Sport, 2016)
Sierpińska Lidia, Zielińska Katarzyna. Zachowania zdrowotne chorych z marskością wątroby = Health behaviours of patients with cirrhosis of the liver. Journal of Education, Health and Sport. 2016;6(8):316-332. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3749115 http://ojs.ukw.edu.pl/index.php/johs/article/view/3762 https://pbn.nauka.gov.pl/sedno-webapp/works/743709 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016. Zachowania zdrowotne chorych z marskością wątroby Health behaviours of patients with cirrhosis of the liver Lidia Sierpińska1, Katarzyna Zielińska2 11 Wojskowy Szpital Kliniczny z Polikliniką SP ZOZ w Lublinie 1 Military Clinical Hospital with Polyclinic, Independent Public Health Care Unit, Lublin 2Studenckie Koło Naukowe Wyższej Szkoły Biznesu i Przedsiębiorczości w Ostrowcu Świętokrzyskim Students’ Scientific Circle, College of Business and Entrepreneurship, Ostrowiec Świętokrzyski Adres do korespondencji: Dr n. med. Lidia Sierpińska 1 Wojskowy Szpital Kliniczny z Polikliniką SP ZOZ, Al. Racławickie 23, 20-904 Lublin, Poland tel. 261183297; fax. 261183277 e-mail: sierpinska1@wp.pl Streszczenie Wprowadzenie. W ostatnich latach obserwuje się wzrost zachorowań na marskość wątroby. Zdaniem specjalistów postępujący proces zwłóknienia komórek wątroby zależy, między innymi, od antyzdrowotnych zachowań. Cel. Rozpoznanie poziomu zachowań zdrowotnych u pacjentów z marskością wątroby. Materiał i metoda. Badaniami objęto 102 dorosłych chorych - 64 mężczyzn i 38 kobiet w wieku 23 – 68 lat, hospitalizowanych w oddziale wewnętrznym, chirurgicznym; leczonych ambulatoryjnie oraz przebywających w zakładzie leczniczo-opiekuńczym. Badania przeprowadzono od stycznia do kwietnia 2016 roku. Metodą badawczą był sondaż diagnostyczny, zaś narzędziem – autorski kwestionariusz ankiety oraz standardowy Inwentarz Zachowań Zdrowotnych (IZZ) wg Juczyńskiego. Wyniki. W badanej grupie u 39,2% chorych wskaźnik zachowań zdrowotnych (IZZ) był przeciętny (5-6 sten), u 31,4% był wysoki (7–10 sten), u 29,5% respondentów był niski (1-4 sten). Dominującym zachowaniem zdrowotnym w badanej grupie było pozytywne nastawienie psychiczne (głównie u kobiet – p<0,01), a najniższy wskaźnik dotyczył codziennych praktyk zdrowotnych (głównie u mężczyzn – p<0,02). Wnioski. Ogólny wskaźnik zachowań zdrowotnych pacjentów z marskością wątroby był przeciętny, a dominującą kategorią było pozytywne nastawienie psychiczne, zaś najniższe wyniki dotyczyły codziennych praktyk zdrowotnych. Konieczne jest rozpowszechnianie edukacji zdrowotnej wśród chorych z marskością wątroby odnośnie codziennych praktyk zdrowotnych oraz prawidłowych nawyków żywieniowych. Edukacją zdrowotną należy objąć szczególnie mężczyzn z niższym wykształceniem, mieszkających na wsi, w wieku powyżej 50 roku życia. Słowa kluczowe: marskość wątroby, zachowania zdrowotne. Summary Introduction. In recent years an increase has been observed in morbidity due to cirrhosis of the liver. According to the specialists, the advancing process of fibrosis of hepatic cells depends, among others, on anti-health behaviours. Objective. Diagnosis of the level of health behaviours in patients with liver cirrhosis. Materials and method. The study included 102 adult patients - 64 males and 38 females, aged 23 – 68, hospitalized in the internal surgical ward, who received ambulatory treatment or stayed in a health care facility. The study was conducted during the period from January – April 2016. The research method was a diagnostic survey, while the instrument – a questionnaire designed by the author, and the standard Health Behaviour Inventory, according to Juczyński. Results. In the examined group, in 39.2% of patients the Health Behaviour Inventory (HBI) was mediocre (5-6 stens), in 31.4% the result was high (7–10 stens), and in 29.5% of respondents - low (1-4 stens). The dominant health behaviour in the group examined was a positive psychol0ogical attitude (mainly among women – p<0.01), whereas the lowest indicator concerned daily health practices (mainly in males – p<0.02). Conclusions. The general indicator of health behaviours of patients with cirrhosis of the liver was mediocre, and the dominant category was a positive psychological attitude, while the lowest results were obtained with respect to daily health practices. It is necessary to spread health education among patients with cirrhosis of the liver, concerning daily health practices and correct nutritional habits. Health education should be especially addressed to males with a lower education level, living in rural areas, and aged over 50. Key words: cirrhosis of the liver, health behaviours.